A General study of Cesaro sequence spaces with Matrix transformations - Pokharel, Jagat Krishna (ILAM इलम, 2023)
In this paper, the researcher utilize the non-absolute type of Cesaro sequence space to transform the Cesaro sequence spaces and establish the necessary and sufficient conditions for the existence of an infinite matrix in the spaces ℓ∞ and C, respectively. When the sequences x∈X satisfy the condition that the series Σ∞k=1 Xk converges, the sequence space H becomes a non-absolute Banach space that fulfills the fundamental requirements for transforming the Cesaro sequence space Xp into the corresponding spaces of ℓ∞ and all convergent sequences. As a consequence of the matrix transformation, some theorems are derived.